The structural and optical properties of Y (Y = Al, B, Si and Ti)-doped ZnO nano thin films from the first principles calculations. (1st December 2017) - Zhang, Wenshu; Hu, Huijun; Zhang, Caili; Li, Jianguo; Li, Yuping; Ling, Lixia; Han, Peide
Abstract: Based on the density functional theory, the structural stability and optical properties of undoped and Y ( Y   =  Al, B, Si and Ti)-doped ZnO nano thin films are investigated. The good stability of the films based on the ZnO (0 0 0 1) can be obtained when the layer is larger than 12. Moreover, the dielectric function, refractive index, absorption, and reflectivity of doped ZnO nano thin films have been analyzed in detail. In the visible light range, the values of ZnO films from 12 to 24 layers are all smaller than those of the bulk. And with the augment of the layers, the values keep increasing. All the results signify that the nano film of 12 layers possesses the lowest reflectivity and weakest absorption. In addition, there is an evident impact of some doped element on the properties of nano films. The absorption and reflectivity of Ti, Si-doped ZnO nano thin films are higher than those of the clean films, while Al, B-doped are lower, especially B-doped. Moreover, the conductivity of the doped structure is better than that of the bulk. Thus, the B-doped ZnO nano thin films could be potential candidate materials of transparent conductive films.